On new fuzzy morphological associative memories. - Wang, S.T (IEEE Transactions on fuzzy systems)
In this paper, the new fuzzy morphological associative memories (FMAMs) based on fuzzy operations (∧,·) and (∨,·) are presented. FMAM with (∨,·) is extremely robust for dilative noise and FMAM with (∧,·) is extremely robust for erosive noise. Autoassociative FMAM has the unlimited storage capability and can converge in one step. The convex autoassociative FMAM can be used to achieve a reasonable tradeoff for the mixed noise. Finally, comparisons between autoassociative FMAM and the famous FAM are discussed. FMAM, as another new encoding way of fuzzy rules, still has a multitude of open problems worthy to explore in the future.